2010
DOI: 10.1073/pnas.0914023107
|View full text |Cite
|
Sign up to set email alerts
|

Specificity landscapes of DNA binding molecules elucidate biological function

Abstract: Evaluating the specificity spectra of DNA binding molecules is a nontrivial challenge that hinders the ability to decipher gene regulatory networks or engineer molecules that act on genomes.Here we compare the DNA sequence specificities for different classes of proteins and engineered DNA binding molecules across the entire sequence space. These high-content data are visualized and interpreted using an interactive "specificity landscape" which simultaneously displays the affinity and specificity of a million-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
151
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 41 publications
3
151
0
1
Order By: Relevance
“…CSI studies demonstrated that affinities and specificities of polyamides for their cognate sites rival the affinities and specificities of natural transcription factors (20)(21)(22)(23). Moreover, CSI data yielded polyamide affinity measurements for every 10-mer sequence that occurs in any given genome (21). Applying this information to map binding potential across the genome led to CSI-based "genomescapes" that predict thousands of putative polyamide-binding sites of varying affinities across the human genome (21,22).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…CSI studies demonstrated that affinities and specificities of polyamides for their cognate sites rival the affinities and specificities of natural transcription factors (20)(21)(22)(23). Moreover, CSI data yielded polyamide affinity measurements for every 10-mer sequence that occurs in any given genome (21). Applying this information to map binding potential across the genome led to CSI-based "genomescapes" that predict thousands of putative polyamide-binding sites of varying affinities across the human genome (21,22).…”
mentioning
confidence: 99%
“…In particular, we developed cognate site identifier (CSI) analysis to interrogate DNA sequence specificity and affinity comprehensively for any given sequence across half a million permutations of a 10-mer binding site (20,21). CSI studies demonstrated that affinities and specificities of polyamides for their cognate sites rival the affinities and specificities of natural transcription factors (20)(21)(22)(23). Moreover, CSI data yielded polyamide affinity measurements for every 10-mer sequence that occurs in any given genome (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28][29] Sequence specificities of Py-Im polyamides have also been investigated by using high-throughput sequencing. [30][31][32] Here, we designed and synthesized thirteen Py-Im polyamides ( Fig.…”
Section: Introductionmentioning
confidence: 99%